Effects of prenatal iron status on child neurodevelopment and behavior: A systematic review. Issue 10 (3rd July 2018) - Iglesias, Lucía; Canals, Josefa; Arija, Victoria
ABSTRACT: Iron deficiency and iron-deficiency anemia are the main worldwide nutritional disorders. A good level of prenatal iron is essential for the correct child neurodevelopment but this association has been poorly investigated. To gather the scientific evidence on the relation between prenatal iron status and child neurodevelopment. To emphasize the importance of personalize the dose and type of supplementation. Wide search strategy was performed in electronic databases for English language articles with no limitations as regards the language or date of publication. Additional studies were selected by hand search. The inclusion criteria were pregnant women without high-risk pregnancy and their children as study population and neurodevelopment as the main outcome. Six RCTs and 13 observational studies were included. The majority concluded that deficit or excess iron during pregnancy injures the mental and psychomotor development of child. Other authors found no association of low iron level with troubles in neurodevelopment, recommended multi-micronutrients instead of iron alone and/or showed inconsistent results. Both iron deficiency as its excess are harmful for the child neurodevelopment. The prenatal iron supplementation should be adjusted for each woman, taking into account the iron stores, some genetic mutation and other health habits.